The Art of the Ancient Near East - Wilkinson, Charles K.
plates: Bronze statuette of goat, Achaemen. period. — Diorite head of Gudea — Diorite head of Ur-Ningirsu, young, beardless, with turban — Sumerian bull's head of copper (2600 В. C.) — Sumerian stone figure from Tell Asmar (2300 В. С.) — Foundation figure of copper (2100 В. C.) — Bronze head of an Elamite ruler from Persia — Stone head of a Sumerian woman (Khafajah?) — Gray pottery pitcher from Sialk (1000 В. C.) — Bronze drinking cup from Luristan (VII century B. C.) — Clay plaques (II millennium В. С.): a god with bull's ears holding lion-headed maces; the sun god appearing over the mountains — Gold necklace found near Babylon (1500 B. C.) — Silver phyton in shape of horse's head (Luristan?) — Silver bowl with cuneiform inscription saying it was made for Artaxerxes I (464-424 B. C.) — Silver bowl with gilded rim from Persia (I century В. С.).